2013
DOI: 10.1002/srin.201200263
|View full text |Cite
|
Sign up to set email alerts
|

Uphill Teeming Utilizing TurboSwirl to Control Flow Pattern in Mold

Abstract: The flow pattern has widely been recognized to have an impact on the exogenous non‐metallic inclusion generation in the gating system and mold flux entrapment in the mold in the uphill teeming process. The possible solutions of the flow pattern control are required to be reliable and practical in order to improve the yield and the ingot quality in the steel production. In this work, a mathematical model of a new novel swirling flow generation component, TurboSwirl, was studied to investigate the flow pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…[19] In the present work, some structural modifications were made based on the divergent nozzle with flaring angle to optimize the flow pattern in order to obtain a more even swirling flow generated by the TurboSwirl device. The first attempt made was to change the flaring angle of the divergent nozzle to minimize the axial velocity and the maximum wall shear stress, and the swirl number was calculated to make sure that the rotation of the liquid steel was strong enough to generate a swirling flow.…”
Section: Haitong Bai Mikael Ersson and Pä R Jö Nssonmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] In the present work, some structural modifications were made based on the divergent nozzle with flaring angle to optimize the flow pattern in order to obtain a more even swirling flow generated by the TurboSwirl device. The first attempt made was to change the flaring angle of the divergent nozzle to minimize the axial velocity and the maximum wall shear stress, and the swirl number was calculated to make sure that the rotation of the liquid steel was strong enough to generate a swirling flow.…”
Section: Haitong Bai Mikael Ersson and Pä R Jö Nssonmentioning
confidence: 99%
“…Moreover, a new swirling flow generator of a much larger scale for steel ingot casting was introduced, called TurboSwirl. [19] It uses the tangential velocity to generate the swirling flow at the intersection of the runners of ingot casting. Studies have been carried out which demonstrate that the filling conditions were much calmer during the initial filling stage, and that this resulted in a lower hump height and a lower maximum wall shear stress.…”
Section: Haitong Bai Mikael Ersson and Pä R Jö Nssonmentioning
confidence: 99%
“…Studies have been done to demonstrate that a much calmer filling condition can be observed during the initial filling stage, which results in a lower hump height and a lower maximum wall shear stress. 15) Moreover, Bai et al 16) showed that it was possible to lower the axial velocity and wall shear stress by changing the flaring angle of the divergent nozzle. Moreover, quite different flow patterns could be obtained when the vertical runner and the divergent nozzle were not placed at the center of the TurboSwirl.…”
Section: An Experimental and Numerical Study Of Swirling Flow Generatmentioning
confidence: 99%
“…In total, five TurboSwirl devices were manufactured. The dimension of the TurboSwirl used in this experiment was taken from Tan,15) but the diameter of the runners was modified from 45 mm to 50 mm due to a restriction in the manufacturing of the plexiglass tubes. The general dimension of the plexiglass TurboSwirl for this experiment is shown in Fig.…”
Section: Water Modelmentioning
confidence: 99%
See 1 more Smart Citation